2020
DOI: 10.1111/tbed.13736
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic tracing and biological characterization of a novel clade 2.3.2.1 reassortant of H5N6 subtype avian influenza virus in China

Abstract: In recent years in China, clade 2.3.4.4 H5N6 plus clade 2.3.2.1 H5N1 subtype highly pathogenic avian influenza (HPAI) viruses have gradually become endemic in poultry, and their co-circulation could inevitably facilitate the gene reassortment between each other. During our routine surveillance in live poultry markets (LPMs) in eastern China in 2017-2018, a novel reassortant H5N6 strain with the HA gene derived from clade 2.3.2.1 was isolated from the cloacal swabs of apparently healthy ducks.Phylogenetic traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, these studies indicated that H9N2 internal genes might contribute to viral dissemination and adaptation. Other than H9N2, LPAIV including H3, H4, and H6 subtypes, were found to participate in the genetic reassortment of H5N6 viruses [ 21 , 31 , 32 ]. Furthermore, several human H5N6 isolates possessed internal genes derived from LPAIV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these studies indicated that H9N2 internal genes might contribute to viral dissemination and adaptation. Other than H9N2, LPAIV including H3, H4, and H6 subtypes, were found to participate in the genetic reassortment of H5N6 viruses [ 21 , 31 , 32 ]. Furthermore, several human H5N6 isolates possessed internal genes derived from LPAIV.…”
Section: Discussionmentioning
confidence: 99%
“…These results and further observations of M807 infections in migratory dabbling and diving ducks are expected to provide a comprehensive understanding of HPAIV ecology in field settings. [11,12]. A clade 2.3.2.1 HPAIV was also isolated from a domesticated Muscovy duck (Cairina moschata) in our surveillance study in Vietnam (A/Muscovy duck/Vietnam/LBM992c/2017 (H5N1); accession numbers: LC656314-21).…”
mentioning
confidence: 85%
“…Although clade 2.3.2.1 HPAIVs have become minor in comparison with the globally circulating clade 2.3.4.4 HPAIVs, they have perpetuated in poultry populations in East Asian countries; Ge et al . reported clade 2.3.2.1 H5N2 and H5N6 HPAIVs in China from 2017 to 2018 [ 11 , 12 ]. A clade 2.3.2.1 HPAIV was also isolated from a domesticated Muscovy duck ( Cairina moschata ) in our surveillance study in Vietnam (A/Muscovy duck/Vietnam/LBM992c/2017 (H5N1); accession numbers: LC656314–21).…”
mentioning
confidence: 99%
“…In avian species, H9N2, H5Nx, and H7N9 are the major subtypes that seriously affect poultry industry worldwide (Carnaccini and Perez 2020 ; Lee et al 2017 ; Lee et al 2021 ). Noteworthy, various HA clades such as clade 2.3.4.4 and clade 2.3.2.1, plus multiple NA subtypes such as H5N1, H5N6, and H5N8, have additionally increased the complexity of the highly pathogenic avian influenza (HPAI) H5Nx viruses (Antigua et al 2019 ; Ge et al 2021 ; Ge et al 2022 ). As for the novel reassortant H7N9 virus which emerged in 2013, it has evolved from low pathogenicity avian influenza (LPAI) to HPAI form and exhibited obvious antigenic variation to challenge the vaccine efficiency (Liu et al 2021 ; Wu et al 2021 ; Yin et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%